Barriers, rather than refugia, underlie the origin of diversity in toads endemic to the Brazilian Atlantic Forest - Thome, Maria Tereza C. [UNESP]; Zamudio, Kelly R.; Haddad, Celio F. B. [UNESP]; Alexandrino, Joao (Wiley-Blackwell, 2014)
In this study, we investigated the relative contribution of geographic barriers and Pleistocene refuges in the diversification of the Rhinella crucifer species complex, a group of endemic toads with a widespread distribution in the Brazilian Atlantic Forest (AF). We used intensive sampling and multilocus DNA sequence data to compare nucleotide diversity between refuge and nonrefuge areas, investigate regional demographic patterns, estimate demographic parameters related to genetic breaks and test refuge versus barrier scenarios of diversification using approximate Bayesian computation. We did not find higher levels of genetic diversity in putative refuge areas, either at regional or biome scale. Rather, the demographic history of the species complex supports regional differences with moderate population growth in the north and central regions and stability in southern AF. Genetic breaks were dated to the Plio-Pleistocene; however, our analyses rejected the role of refuges in creating a northern and central divergence, supporting a recent colonization scenario at a smaller scale within the central AF. Overall, our data rule out massive climatically driven fragmentation and large-scale recolonization events for populations across the biome. We confirmed the importance of geographic barriers in creating main divergences and underscored the importance of searching for cryptic discontinuities in the landscape. Comparison of our results with those of other AF taxa indicates organismal specific responses to moderate shifts in habitat and that multiple refuges may constitute a more realistic model for diversification of Atlantic Forest biota.
Keywords: Diversification; Habitat fragmentation; Phylogeography; Rhinella crucifer group